Influence of Green Accounting and Environmental Performance on Firm Value with Good Corporate Governance as a Moderating Variable - Chotimah, Nurul; Nuryana, Ita (SAFE-Network, 2026)
This study aims to examine the effect of green accounting and environmental performance on firm value, as well as the role of good corporate governance as a moderating variable. The study was conducted on energy sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. Secondary data were obtained from companies' annual reports and sustainability reports, then analyzed using Moderated Regression Analysis (MRA) with the help of Eviews 13 2025. The results show that green accounting and environmental performance do not have a significant effect on firm value. However, good corporate governance can moderate the relationship between green accounting and environmental performance on firm value. These findings indicate that the implementation of good corporate governance can strengthen the relationship between environmental management practices and company value, so that companies are expected to be able to integrate sustainability and governance aspects more optimally in increasing company value.